Battery Management System (BMS) Planning on Quadcopter Flying Electric Vehicle - Mochammad Bilal Al Kahvi; Sugeng Hadi Susilo (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
Electric Vehicle Flying (KLT) quadcopter is an emerging technology that has great potential for various applications. The battery is one of the important components in the quadcopter KLT, and the battery management system (BMS) plays an important role in maintaining the performance, safety, and service life of the battery. This study aims to design, determine the wiring design and test the performance of the BMS on a quadcopter flying electric vehicle. Methods: This study is to design a battery management system (BMS) for a flying electric vehicle and then test it to see its effect on the performance of the electric motor and the safety of the battery Results: Based on testing when the battery management system is on standby, it shows that the battery is in good condition and has sufficient capacity. The battery voltage is within the normal range, the battery current is not flowing, the battery power is unused, the average cell voltage is normal, and the remaining battery capacity is almost full. The Jikong BMS is functioning properly and the battery is in good condition. Conclusion: The planning of the battery management system (BMS) on the quadcopter flying electric vehicle was successfully made with adjustments to the Battery LifePo4 used.